Case report: Spontaneous coronary artery dissection in a man with Ehlers–Danlos syndrome - Li, Qiao; Ma, Min; He, Yong (Frontiers in Cardiovascular Medicine, 2022)
Background Spontaneous coronary artery dissection (SCAD) is an emergency and non-atherosclerotic cause of acute coronary syndrome (ACS). It often occurs in young to middle-aged women and rarely in men. This emergency is easily misdiagnosed and missed and has a high in-hospital mortality rate. Case summary Here, we report a young male patient who was admitted to the emergency department due to chest pain. During hospitalization, we use imaging modalities, genetic analysis, and clinical strategy in the diagnosis, and management of a male patient with SCAD and was diagnosed with vascular Ehlers-Danlos syndrome (vEDS). Unfortunately, the patient died of sudden cardiac death (SCD) on the ninth day from the index spontaneous coronary artery dissection (SCAD) event before reporting the DNA analysis results. Despite huge progress in the clinical characterization of SCAD from an international effort, assess and follow-up patients, this remains a condition for which the pathophysiology is poorly understood and for which, despite a significant recurrence risk, there is no specific disease-modifying therapy. Conclusion vEDS is a rare cause of SCAD,which is an inherited connective tissue disorder, manifesting as congenital connective tissue dysplasia, is a rare and particularly challenging monogenetic disease, which causes arterial dissections and ruptures that can lead to early death due to COL3A1 pathogenic variants. The gold standard for SCAD diagnosis is CAG.